Outlining the Molecules Tested In Vivo for Chagas Disease, Malaria, and Schistosomiasis Over the Last Six Years - A Literature Review Focused on New Synthetic Drug Identities and Repurposing Strategies - de Melo Silva, Vanessa G.; da Concei, Juliana Maria; Vieira Costa Silva, Carla Cauanny; Leal, Amanda Calazans; SNM, DanielLopesAra&; Nunes, Janine Siqueira; da Silva, Elineide T. N.; da Silva, Firmino Santos; de Barros Dias, Mabilly Cox Holanda; Lima Leite, Ana Cristina (Current Medicinal Chemistry, 2023)
Background: COVID-19 disrupted NTD programs in 60% of countries, impairing public health goals. Thus, boosting NTD's research knowledge is demanding, and in vivo screening of candidates allows for the prospect of promising options based on their overall profile. Objective: In this work, we highlighted the relevant research done between 2015-2021 in the fields of synthetic and repurposed drugs that were tested in vivo for Chagas disease, malaria, and schistosomiasis. Methods: MEDLINE, PUBMED, CAPES PERIODIC, and ELSEVIER databases were used for a comprehensive literature review of the last 6 years of research on each area/disease. Results: Overall, research focused on nitro heterocyclic, aromatic nitro, nucleoside, and metal-based scaffolds for analogue-based drug generation. Repurposing was widely assessed, mainly with heterocyclic drugs, their analogues, and in combinations with current treatments. Several drug targets were aimed for Chagas treatment, specific ones such as iron superoxide dismutase, and more general ones, such as mitochondrial dysfunction. For malaria, hemozoin is still popular, and for schistosomiasis, more general structural damage and/or reproduction impairment were aimed at in vitro analysis of the mechanism of action. Conclusion: Latest in vivo results outlined trends for each disease - for Chagas Disease, heterocyclics as thiazoles were successfully explored; for Malaria, quinoline derivatives are still relevant, and for schistosomiasis, repurposed drugs from different classes outstood in comparison to synthetic compounds. This study uprises the continuous development of Chagas disease, malaria, and schistosomiasis drugs, providing researchers with tools and information to address such unmet therapeutic needs.
Keywords: synthetic compounds